(untitled) (Bangladesh Journal of Agricultural Research, 2026)
A field research was carried out durig 2014-15and 2015-16, using eight white maize inbred lines (CML154, VL109196, CML491, VL05590, CML502, CLRCWQ10, CLRCWQ26 and CML511) designated as P1, P2, P3, P4, P5, P6, P7 and P8 respectively, to estimate the combining ability effects and heterosis of 28 crosses produced following half diallel mating design at Bangladesh Agricultural Research Institute, Gazipur, Bangladesh. Assessment was done for eight characters viz. days to pollen shedding, days to silking, plant height, ear height, ear length, number of grains/ear, 1000 -grain weight and yield. Considering overall performance of GCA effects observed that parent P6 was the best general combiner for both yield and earliness while parent P2 and P8 for dwarfness. Two hybrids namely, P3×P5 and P6×P8 exhibited significant positive SCA effects and significant positive heterosis for grain yield. These two hybrids were selected for future trial. Bangladesh J. Agril. Res. 48(1): 115-124, March 2023